Poster: Smart networked bicycles with platoon cooperation (2015)
Urban roads are venues of social interaction where many actors try to accomplish their transportation-related individual goals. It has been demonstrated that when individuals act with scarce contextual information they offer resistance to one another's programs of action hindering coordination. In this work we address the problem of smart networked bicycles assisting cyclist coordination. Coordination is based on vehicular communications together with a cooperative adaptive cruise control. We propose to combine effective dissemination mechanisms in mesh-networks, a platoon cooperation logic, and a novel cyclist-bicycle interface to adapt the behaviour of cyclists while driving. Initial simulations and experimental results demonstrate that our cooperation mechanism helps cyclists achieve individual and collective goals, such as moving fluidly at the best possible speed while maintaining a safe distance to other cyclists.